LIFE TABLES AND POPULATION PARAMETERS OF HELOPELTIS ANTONII (HEMIPTERA: MIRIDAE) REARED ON CASHEW (ANACARDIUM OCCIDENTALE L.) - Siswanto; Rita Muhamad; Dzolkhifli Omar; Elna Karmawati (Tropical Life Sciences Research, 2008)
Survivorship and fertility of Helopeltis antonii were measured under laboratory and field condition in Wonogiri, Indonesia. Life tables and population parameters for the mirid were constructed based on unlimited food condition and a natural enemies-free environment. The highest mortality occurred in the immature stage, especially on first and second instar of nymphal stages. The survival from egg to adult emergence were about 0.92. The proportion of female to male observed was 1:0.92. The females could live for a maximum of 24 days. Oviposition trend with peak at the end of the female life span. The mean number of eggs produced per female was 6.8. The intrinsic rate of increase (rm) was 0.092 per female per day and daily finite rate of increase (?) was 1.097 females per female per day, with mean generation time (T) was 27.70 days. The net reproductive rate (Ro) of the population was 12.84. The population double time (DT) was within 7.52 days. Kadar kemandirian dan fertiliti Helopeltis antonii telah dibuat di makmal dan di ladang di Wonogiri, Indonesia. Jadual hidup dan parameter populasi mirid dibuat berdasarkan pada keadaan makanan yang tak terbatas dan bebas dari musuh semula jadi. Mortaliti tertinggi didapati pada peringkat muda, terutama pada peringkat nimfa satu dan dua. Kemandirian dari peringkat telur hingga serangga dewasa ialah 0.92. Nisbah jantina betina kepada jantan ialah 1:0.92. Betina dewasa dapat hidup maksimum selama 24 hari. Corak oviposisi dengan pemuncak didapati pada akhir kehidupan betina. Purata telur yang dihasilkan per betina dewasa ialah 6.8. Kadar pertambahan intrinsik semula jadi (rm) ialah 0.092 per betina per hari dan kadar pertambahan finit harian (?) ialah 1.097 betina per betina per hari, dengan purata waktu generasi (T) ialah 27.70 hari. Kadar pembiakan net untuk populasi bersangkutan (Ro) ialah 12.84. Waktu penggandaan populasi (DT) ialah 7.52 hari.